PHYSICO-CHEMICAL QUALITY CONTROL AND DOSAGE OF TOTAL POLYPHENOLS, FLAVONOIDS OF Morus alba LEAVES (MORACEAE) - Pereira, Camila Bugnotto; Marin, Aline; Necchi, Raquel Medina Martins; Maki, Tiago Trevisan; Manfron, Melânia Palermo (Saúde (Santa Maria), 2012)
To establish parameters for quality control ofMorus alba leaves were done tests of purity by determining the loss on drying, foreign matter, total ash, acid insoluble ash, swelling index, bitterness index, yield of crude extract, pH and organoleptic properties. The tests were done with samples collected on March, June, September and December, which were according to Brazilian Pharmacopeia and World Health Organization.Through 70 % ethanol extracts of M. alba leaves it was done the dosage of total polyphenols and flavonoids, which were used, respectively, the acidgallic and rutin standards.